Impact of personal economic environment and personality factors on individual financial decision making - Prinz, Susanne; Gründer, Gerhard; Hilgers, Ralf D.; Holtemöller, Oliver; Vernaleken, Ingo (Frontiers in Psychology, 2014)
This study on healthy young male students aimed to enlighten the associations between an individual’s financial decision making and surrogate makers for environmental factors covering long-term financial socialization, the current financial security/responsibility, and the personal affinity to financial affairs as represented by parental income, funding situation and field of study. A group of 150 male young healthy students underwent two versions of the Holt and Laury (2002) lottery paradigm (matrix and random sequential version). Their financial decision was mainly driven by the factor ‘source of funding’: students with strict performance control (grants, scholarships) had much higher rates of risk aversion (RRA) than subjects with support from family (RRAdiff=0.22; p=0.018). Personality scores only modestly affected the outcome. In an ANOVA, however, also the IQ significantly and relevantly contributed to the explanation of variance; the effects of parental income and the personality factors ‘agreeableness’ and ‘openness’ showed moderate to modest – but significant - effects. These findings suggest that environmental factors more than personality factors affect risk aversion.